Diagnostic profiles and predictors of treatment outcome among children and adolescents attending a national psychiatric hospital in Botswana. Issue 1 (December 2017) - Olashore, Anthony; Frank-Hatitchki, Bechedza; Ogunwobi, Olorunfemi
Abstract Background Attention is currently being drawn to child psychiatric care, most especially in the developed countries. This type of care is still rudimentary in the developing countries. Botswana is one of the African countries with good health care services but mental illness is given the low priority. Child and adolescent mental health care (CAMHC) is almost non-existent likely due to the dearth of research which would drive a policy change in this direction. Hence the need for this research as a step towards establishing a well-structured CAMHC. Objectives To determine the pattern of presentation of child psychiatric disorders and the predictors of poor treatment outcome in the national psychiatric hospital in Botswana. Methods This is a retrospective investigation comprising patients aged ≤17 years, consulting Sbrana Psychiatric Hospital over a 5-year period. It involves extraction of information from 238 patients' records on socio-demographic characteristics, diagnosis and management. Results The most common diagnosis was Attention deficit hyperactivity disorder (ADHD) with a prevalence of 25.2%. ADHD (60%) and Autism (58.3%) were more diagnosed in 5–9 years, whilst psychosis (80%) and depression (88.9%) amongst 14–17 years. Perinatal complication (OR 7.326, 95% CI: 1.312–40.899) and polypharmacy (OR 4.188, 95% CI: 1.174–14.939) independently predicted poor treatment outcome, after logistic regression. Conclusions This study provided baseline information regarding children mental health in Botswana. It highlights the need for further research and to develop more specialized mental health care services for improved outcomes in children with mental health disorders.